PENGEMBANGAN MEDIA BOOKLET DIGITAL TENTANG CERDIK UNTUK PENCEGAHAN DIABETES MELITUS DI SMPN 3 LEMBANG - Nabila, Chandrika (Jurnal Kesehatan Siliwangi, 2024)
Background: West Bandung Regency is one of the districts with a high prevalence of Diabetes Mellitus, one of the causes of Diabetes Mellitus in adolescents is the lack of health education about the prevention of Diabetes Mellitus through educational media. Therefore, digital booklet media is needed to facilitate the provision of health education about CERDIK. Objective: To produce the development of digital booklet media about ingenuity for the prevention of diabetes mellitus at SMPN 3 Lembang which can be used in health education. Method: This study using the 4D model (Define, Design, Development, Disseminate) and data collection is carried out by in-depth interviews and questionnaires. Media development was carried out to media experts, material experts, and user tests to 90 grade 8 students through questionnaires to user tests and data analysis using the feasibility percentage formula. Results: The define stage was carried out by interviewing 5 students with the needs of digital booklet media that they wanted informative, easy-to-understand language, and attractive colors, the design stage by designing media, the development stage showed the results of the feasibility test from 94% media experts, 81% material experts, and 96% users, meaning that the media was very suitable for use. The disseminate stage of digital booklet media can be disseminated and can be used. Conclusion: Digital booklet media is very feasible to be used as a prevention of Diabetes Mellitus in grade 8 students at SMPN 3 Lembang.